Model Empiris Impor Garam Indonesia - Abdul Hakim; Anissa Triyanti (Jurnal Manajemen dan Organisasi, 2020)
Indonesia is the fourth longest coastal country in the world, so it has the potential to become a salt exporting country. But appareantly, Indonesia has very high salt imports. This paper seeks to raise the irony bya modeling Indonesian salt imports. Based on various theories and result of previous studies, this paper proposes the price of imported salt, the real exchange rate, the need for salt, and domestic production as an independent variable. The sample used stretches from 2001 to 2018. This paper uses a time series model to analyze data. With the conditional ECM (error correction model), this paper finds that in the short or long term, all selected independent variables have a significant effect on the volume of salt imports, although the exchange rate requires lag to influence the import. This paper suggests increasing the education of salt farmers related to the salt content desired by industry.